Genetic IS901 RFLP diversity among Mycobacterium avium subsp. avium isolates from four pheasant flocks - Moravkova, Monika; Lamka, Jiri; Slany, Michal; Pavlik, Ivo (Journal of veterinary science, 2013)
IS901 RFLP analysis of 36 Mycobacterium avium subsp. avium (MAA) isolates from 15 pheasants (Phasianus colchicus) and two goshawks (Accipiter gentilis) from four pheasant farms was performed. Using this method, six different IS901 RFLP types (E, F, G, M, Q, and V) were identified. The distribution of IS901 RFLP profiles was tightly linked to individual flocks. Matching IS901 RFLP profiles observed in the present study indicate MAA transmission between pheasants and goshawks in the same locality. In two flocks, different pheasants within a flock as well as in various organs of five individual pheasants were found to have two distinct IS901 RFLP profiles.
Keywords: Poultry Diseases; střeva; slezina; Galliformes; polymorfismus genetický; Tuberculosis, Avian; Polymorphism, Genetic; Spleen; nemoci drůbeže; Animals; játra; Mycobacterium avium; zvířata; Bone Marrow; kostní dřeň; polymorfismus délky restrikčních fragmentů; Intestines; Liver; Polymorphism, Restriction Fragment Length; ptačí tuberkulóza